EFFECTIVENESS OF GARLIC WATER EXTRACT GEL (ALLIUM SATIVUM. L) AGAINST NECROTIC FACTOR ALFA TUMORS AND MOUTH ULCER DIAMETER IN WISTAR WHITE MALE RATS - Anggraeni, Dian; Kamaluddin, Kamaluddin; Theodorus, Theodorus (Biomedical Journal of Indonesia, 2020)
Oral ulcers are pathological conditions that are characterized by loss of epithelial tissue, causing inflammation. During inflammation, the inflammatory mediator is TNF will increase. Therefore, drugs are needed to suppress TNF-levels to suppress inflammation. One of the herbal ingredients that can suppress inflammation is garlic. In vivo laboratory experimental research with pre-post systems. The samples used were 36 male Wistar white rats divided into 6 groups (6 individuals / groups), namely the group without drug treatment (as pre-treatment data), negative control group namely HPMC gel base, positive control given benzydamin, group treatment I was given a garlic water extract gel 20%, treatment group II was given a garlic water extract gel 40%, treatment group III were given a garlic water extract gel 80%. The drug is given topically 2 times a day for 4 days. Making oral ulcers is done by placing filter paper that has been soaked in a 50% acetic acid solution in the labial area of the mandibular gingival tissue. Measurement of oral ulcers was performed on the 1st day after the manufacture of oral ulcers and the 5th day. On the 5th day all the mice were sacrificed to be taken gingival tissue and TNF-levels were measured. using ELISA. Data analysis using SPSS version 24 and One Way Anova test with 5% specification followed by Post Hoc Test using LSD test and Games Howell. Analysis using One Way Anova showed that there were significant differences in TNF-levels and the diameter of the oral ulcer (p <0.05) between groups which indicated that the garlic water extract gel applied in the area of the oral ulcer affected TNF levels. and the diameter of the oral ulcer. LSD test results showed that 80% effective garlic water extract gel significantly reduced TNF levels. (p <0.05). Games Howell test results showed that 20%, 40% and 80% garlic water extract gel had the same effectiveness as benzydamin in decreasing the diameter of oral ulcer. Garlic water extract gel (Allium sativum. L) concentration was 80% more effective than benzydamin for decreasing TNF levels Garlic water extract gel (Allium sativum. L) concentrations of 20%, 40% and 80% are as effective as benzydamin in reducing the diameter of oral ulcers in male wistar strain rats.